Can the intensity of playing online games affect interest in learning? - Siti Nur Faizatul Iqlimah; Hazim Hazim (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The different levels of student interest in learning and also the influencing factors, including of playing online games. How often the students spend their time playing online games and whether or not they have high interest in learning. This research aims to determine the relationship between the intensity of playing online games and students interest in learning at MI Darul Fikri Wonoayu. The hypothesis of this research is that there is a relationship between the intensity of playing online games and students interest in learning at MI Darul Fikri Wonoayu. This research uses a quantitative approach with product moment correlation approach. The sample in this research was 31 students and the data was taken by using purposive sampling technique. This research consists of 35 scale items uses an intensity scale for playing online games and a scale for the students learning interest. The results of the research show that there is a significant relationship between the intensity of playing online games and students learning interest in MI DArul Fikri Wonoayu, with a coefficient value of 0,3044. Thus, the hhigher the intensity of the students plaing online games, the lower the students interest in learning. In contrast, the lowerthe intensity of playing online games, the higher the students interest in learning. Tingkatan minat belajar siswa yang berbeda-beda dan juga factor-faktor yang mempengaruhiinya, sebagai contoh intensitas bermain game online. Seberapa sering siswa ini menghabiskan waktunya untuk bermain game online dan seberapa tinggi minat belajar yang dimiliki siswa. Penelitian ini emiliki tujua untuk mengetahui adanya hubungan antara intensitas bermain game online terhadap minat belajar siswa di MI Darul Fikri Wonoayu. Hipotesis penelitian yaitu adanya hubungan antara intensitas bermain game online dengan minat belajar siswa di MI Darul Fikri Wonoayu. Penelitian ini menggunakan pendekatan kuantitatif, dengan korelasi product moment. Sampel dalam penelitian ini berjumlah 31 orang siswa, dengan teknik pengambilan sampel yaitu purposive sampling. Skala yang digunakan dalam penelitian ini yaitu model skala likert, dengan jumlah 35 butir soal yang menggunakan skala intensitas bermain game online dan skala minat belajar siswa. Hasil penelitian ini menunjukkan adanya hubngan signifikan antara intensitas bermain game online dengan minat belajar siswa di MI Darul Fikri Wonoayu, dengan nilai koefisien 0,3044. Maka semakin tinggi intensitas bermain game online maka semakin rendah minat belajar siswa, begitupun sebaliknya semakin rendah intensitas bermain game online maka semakin tinggi minat belajar siswa di MI Darul Fikri Wonoayu.